Grazer exclusion is associated with higher fast-cycling carbon pools but lower slow-cycling mineral-associated carbon across grasslands - Luhong Zhou; Shangshi Liu; Maarten Schrama; Deborah Ashworth; Richard D. Bardgett (Proceedings of the National Academy of Sciences, 2026)
The removal of livestock grazers from historically grazed grasslands is widely proposed as a key strategy for the enhancement of soil organic carbon (SOC) for climate mitigation. Yet, accurate assessments of how grazer exclusion impacts SOC pools of differing stability are lacking, with most studies focusing on total SOC rather than the distribution of SOC within fast and more stable, slow-cycling pools. Here, we used 12 historically grazed grassland sites along an 800 km south–north gradient across the United Kingdom to test how particulate (POC) and mineral-associated organic carbon (MAOC) pools were linked to long-term (>10 y) exclusion of large domesticated grazers. We found that grazer exclusion was associated with relatively higher fast-cycling C pools, including plant and litter C, and to a lesser extent POC, but lower more stable, slow-cycling MAOC pools compared to grazed controls. Grazer exclusion was also associated with a marked shift in vegetation composition, with greater cover of ericoid mycorrhizal (ErM) shrubs over arbuscular mycorrhizal (AM) graminoids. This vegetation shift likely played a dual role in regulating SOC, contributing to higher POC via both the input of recalcitrant litter and by the enhancement of soil moisture and lower MAOC due to priming and decreased mineral protection of SOC. Our findings provide evidence that while the exclusion of grazers tends to favor fast-cycling C pools, it coincides with lower SOC persistence, potentially increasing the vulnerability of grassland SOC stocks to future climate change.